Synthesis and Spectroscopic Characterization of a New Series of Tetrazole Compounds - Bana S. Abdulrahman; Roshna B. Nadr (Zanco Journal of Pure and Applied Sciences, 2022)
The current study involves synthesis and characterization of a new family of tetrazole derivatives. The synthetic pathway includes two steps, as described here: Initial step was synthesis of N-(4-(6-methylbenzothiazol-2-yl) phenyl)-1-(substituted phenyl)methanimine (1-7), via the reaction of 4-(6-methylbenzothiazol-2-yl)aniline with a variety of substituted benzaldehydes in absolute ethanol utilizing glacial acetic acid as catalyst. The next step was synthesis of tetrazole derivatives (8-14) by the reaction of the synthesized imines (1-7) with sodium azide in dry dioxane. Spectroscopic methods (FT-IR, 1H-NMR and 13C-NMR) were used to determine the structures of the produced products. The synthesized compounds were tested for antibacterial activity against two types of bacteria Staphylococcus aureus (Gram +ve) and Escherichia coli (Gram -ve). The results showed good activities against both types of bacteria.